A flavonoid 3-O-glucoside:2″-O-glucosyltransferase responsible for terminal modification of pollen-specific flavonols in Arabidopsis thaliana - Yonekura-Sakakibara, Keiko (Plant J, 2014)
Flavonol 3-O-diglucosides with a 1→2 inter-glycosidic linkage are representative pollen-specific flavonols that are widely distributed in plants, but their biosynthetic genes and physiological roles are not well understood. Flavonoid analysis of four Arabidopsis floral organs (pistils, stamens, petals and calyxes) and flowers of wild-type and male sterility 1 (ms1) mutants, which are defective in normal development of pollen and tapetum, showed that kaempferol/quercetin 3-O-β-d-glucopyranosyl-(1→2)-β-d-glucopyranosides accumulated in Arabidopsis pollen. Microarray data using wild-type and ms1 mutants, gene expression patterns in various organs, and phylogenetic analysis of UDP-glycosyltransferases (UGTs) suggest that UGT79B6 (At5g54010) is a key modification enzyme for determining pollen-specific flavonol structure. Kaempferol and quercetin 3-O-glucosyl-(1→2)-glucosides were absent from two independent ugt79b6 knockout mutants. Transgenic ugt79b6 mutant lines transformed with the genomic UGT79B6 gene had the same flavonoid profile as wild-type plants. Recombinant UGT79B6 protein converted kaempferol 3-O-glucoside to kaempferol 3-O-glucosyl-(1→2)-glucoside. UGT79B6 recognized 3-O-glucosylated/galactosylated anthocyanins/flavonols but not 3,5- or 3,7-diglycosylated flavonoids, and prefers UDP-glucose, indicating that UGT79B6 encodes flavonoid 3-O-glucoside:2″-O-glucosyltransferase. A UGT79B6-GUS fusion showed that UGT79B6 was localized in tapetum cells and microspores of developing anthers.